EVALUASI KESESUAIAN LAHAN UNTUK PADI SAWAH TADAH HUJAN (Oryza sativa L.) DI KECAMATAN MUARA KABUPATEN TAPANULI UTARA - Yopie Priest Aulia Sinaga; Razali Razali; Mariani Sembiring (Universitas Sumatera Utara, 2014)
This study aimed to evaluate the suitability of land in Muara North Tapanuli for rainfed paddyfields. Based on a map of soil type and slope maps generated from topographic maps with a scaleof 1: 50,000, then be overlaid. Raised 3 LMU(Land Map Unit) are eligible to be assessed for rainfedpaddy crop. The assessment of land suitability classes with appropriateness rainfed paddy fieldscriteria is based on Djaenuddin, et al., 2011. The results showed that the potential land suitabilityclass LMU 1 isN (rc), potential land suitability class LMU 2 is S3 (tc), potential land suitabilityclass LMU 3 is S3 (tc, rc). Potential land area for rainfed paddy fields in the district of Muara is of1844 hectares.